Media Pembelajaran Interaktif untuk Meningkatkan Minat Siswa Belajar Matematika di SMA Negeri 1 Tayan Hulu - Hendratmoko, Yayan; T, Ahmad Yani; Siregar, Nurfadilah; Meldi, Nadya Febriani; Afni, Nur; Rahmawati, Dian (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The interest in learning mathematics among students is still considered low, with many students perceiving this subject as difficult. Learning interest is a crucial factor for achieving academic success, prompting educators to innovate and be creative in their teaching methods. One approach that can enhance student engagement is the use of interactive and appealing learning media. This study utilized the Quizizz application with the Lesson feature to explore its impact on students' interest in learning in the 12th grade at SMAN 1 Tayan Hulu. The method employed in this research is quantitative, using a quasi-experimental design with a Posttest Only Control Design model. Sampling was conducted using a Nonprobability Sampling technique, and the research instrument consisted of a questionnaire containing 25 positive statements. Data analysis was performed using SPSS Statistics 25.0 for Windows to conduct normality tests with the Kolmogorov-Smirnov method, homogeneity tests with Levene, and hypothesis testing using a t-test with a significance level of 0.05. The analysis results indicated that the t-value of 8.768 was greater than the t-table value of 2.011, indicating a significant effect of using Quizizz as an interactive media on students' interest in learning mathematics. Thus, this study demonstrates that interactive media can positively contribute to increasing students' interest in learning.